Bronchoalveolar lavage hemosiderosis in dogs and cats with respiratory disease. (18th January 2019) - Hooi, Kimberly S.; Defarges, Alice M.; Jelovcic, Stipe V.; Bienzle, Dorothee
Abstract : Background: Hemosiderophages can be found in bronchoalveolar lavage samples and have been reported in association with a wide range of respiratory and cardiovascular disorders in cats and humans. Objectives: This study aimed to retrospectively evaluate the presence of hemosiderin in canine and feline bronchoalveolar lavage (BAL) samples. It also aimed to examine the association of BAL hemosiderin with signalment, clinical signs, and historical disease prior to BAL, with prior transthoracic fine‐needle aspiration (FNA), with bronchoalveolar lavage duration, and with cytologic interpretation. Methods: The medical records of dogs and cats with respiratory disease that underwent BAL between 2007 and 2016 were reviewed. Appropriate medical information and BAL results were available from 171 dogs and 34 cats. Cases were assigned to four disease categories based on BAL cytologic findings: pneumonia, inflammatory disease, neoplasia, or normal airways. The degree of hemosiderosis was classified based on a semi‐quantitative scoring scale. Exact logistic regression analysis was used to evaluate the relationship between risk factors and the presence of BAL hemosiderosis on cytology. Results: Hemosiderin was identified in 13/171 (7.6%) canine samples and 18/34 (52.9%) feline samples. Cats were 13.33 times more likely to have pulmonary hemosiderosis on bronchoalveolar lavage cytology compared with dogs ( P < 0.001). Increased respiratory rates, prolonged bronchoalveolar lavage times, concurrent transthoracic FNAs, and cytologic diagnoses were associated with an increased risk of hemosiderosis in dogs. No specific risk factors associated with pulmonary hemosiderosis in cats were identified. Conclusions: Hemosiderosis is more common in BAL samples from cats than from dogs and is associated with a diverse range of disease conditions.